Performance of VoIP Using Routing Open Shortest Path First with Multi-Protocol Label Switching - Danang Sunandar; Abdi Wahab; Mudrik Alaydrus (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2021)
Voice over internet protocol is a communication technology in the world of computer network that can be used for sending voice or video and data transmission over Internet Protocol in real time. VoIP network can be implemented with Asterisk applications as a server to a Private Automatic Branch eXchange applied in a Graphical Network Simulator 3. In this study, VoIP communication using routing OSPF within MPLS will be calculated, the QoS value collected based on impact performance under normal condition and not normal condition (link failure) different varian bandwidth in the network. The results from the simulation show that in normal condition and not normal condition there is average delay value with routing OSPF 4 ms and routing OSPF with MPLS 5 ms, the value of jitter max which same of 6 ms using varian bandwidth from 256 kbps and 512 kbps. All of the QoS parameters, such as delay, jitter and packet loss will be compare to standard ITU-T G.114. This research can be extended with addition of another measurement or another protocol.